(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Material management system involves procurement, storage, identification, retrieval, transport and construction methods. Each is indelibly linked to safety, productivity and schedule performance. The main objective of our research is to analyze the Material management control adopted and the effective utilization of Material at the construction site. ABC analysis is one of the conventionally used approaches to classify the inventories and the case study of a company is collected. The tracking and locating of materials in construction jobsites has increase a great concern among construction entities. The improper handling and storage of materials in construction site has made it difficult to track and locate materials when the time they are needed. These findings may reflect the main factors that will affect the Material management system which able to achieve the improved efficiency of project management and to reduce the waste of materials in the respective region of construction industries.